PENGEMBANGAN PRODUKTIFITAS SUMBER DAYA MANUSIA DENGAN PENDEKATAN UJI KOMPETENSI DAN PEMBINAAN COACHING - Ashari, Muhamad Roby; Sandra, Muhammad Yopfie; Syadzili, Ahmad; Victorynie, Irnie (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Two of the many methods of human resource development are using competency tests and Coaching. Many organizations do not find the key to the failures they face, they assume the team or members are not working optimally. Whereas it is very possible that unproductivity occurs because the placement of personnel is not in accordance with their capacity, and there is no proper Coaching of personnel who carry out activities repeatedly even though mistakes always occur. Therefore, it is important to develop human resources with a competency test and Coaching approach. With this method, employees are expected to be able to maximize their potential and feel the expected comfort. So as to produce conditions where the right people are in the right place and maximize all abilities to give their best to the organization and contribute to the development of human resources around them.